Self-efficacy and social support have relationship with academic burnout in college nursing students - admin; Firdausi, Alfia Nuriil; Fitryasary, Rizki I; Tristiana, Dian; Fauziningtyas, Rista; Thomas, Deena Clare (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the relationship of self-efficacy and social support with academic burnout of nursing students. Method: The correlational, cross-sectional study was conducted in August 2021 at the Faculty of Nursing, Universitas Airlangga, Surabaya, Indonesia, and comprised nursing students in the 4th and 6th semesters of their academic programme. Data was collected using self-efficacy and social support questionnaires as well as the Maslach Burnout Inventory-Student Survey. Results: Of the 184 subjects, 160(87%) were females and 24(13%) were males; 98(43.3%) were from the 4th semester and 86(46.7%) were from the 6th; 66(36.4%) were aged 20 years, followed by 65(35.9%) aged 21 years; and East Java was the hometown for 163(88.6%) students. Self-efficacy (p=0.005; r=-0.205) and social support (p=0.000; r=-0.265) were significantly associated with academic burnout. Conclusion: Higher self-efficacy and social support levels may lead to lower academic burnout among nursing students. Keywords: Self-efficacy, Burnout, Psychological, Social support, Nursing.